2018
DOI: 10.1097/aln.0000000000002417
|View full text |Cite
|
Sign up to set email alerts
|

Brain Dynamics and Temporal Summation of Pain Predicts Neuropathic Pain Relief from Ketamine Infusion

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Ketamine is an N-methyl-d-aspartate receptor antagonist that reduces temporal summation of pain and modulates antinociception. Ketamine infusions can produce significant relief of neuropathic pain, but the treatment is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 47 publications
1
57
0
1
Order By: Relevance
“…Becerra reported that ketamine coma therapy recovered the altered brain functional network of patients with chronic pain, and the recovered state had paralleled as default networks of healthy volunteers 32 . Rachael reported that patients with refractory neuropathic pain who was treated with ketamine (0.5 to 2 mg/kg/h; mean dose 1.1 mg/kg/h) for 6 hour/day for 5 consecutive days 33 . They reported that approximately 50% of patients had a reduction in NRS of 30% or greater at 1 month after intravenous ketamine infusion, and the relationship between temporal summation of pain and pain relief is mediated by default mode network–descending antinociceptive pathway dynamic functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Becerra reported that ketamine coma therapy recovered the altered brain functional network of patients with chronic pain, and the recovered state had paralleled as default networks of healthy volunteers 32 . Rachael reported that patients with refractory neuropathic pain who was treated with ketamine (0.5 to 2 mg/kg/h; mean dose 1.1 mg/kg/h) for 6 hour/day for 5 consecutive days 33 . They reported that approximately 50% of patients had a reduction in NRS of 30% or greater at 1 month after intravenous ketamine infusion, and the relationship between temporal summation of pain and pain relief is mediated by default mode network–descending antinociceptive pathway dynamic functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Of all mentioned NMDAR antagonists, ketamine is possibly most efficacious in reducing windup and temporal summation [12]. In a recent study in patients with refractory NP, temporal summation measured just before treatment was a predictor of the efficacy of ketamine [13].…”
Section: Treatment Of Neuropathic Painmentioning
confidence: 99%
“…Further, results of clinical studies in chronic pain investigating treatment-induced functional brain changes show some overlap with neural changes related to pain-related fear and experimental fear extinction (e.g., implicating the amygdala, mPFC, and PAG) (Baliki et al, 2008; Becerra et al, 2014; Erpelding et al, 2014; Simons et al, 2014). The majority of treatment studies focused on intrinsic brain activity, i.e., in rest and without a specific task (Napadow et al, 2012; Harris et al, 2013; Bosma et al, 2018). The effects of EXP specifically have also only been investigated using resting-state fMRI (Zhu et al, 2018), showing that patients with post-traumatic stress disorder showed enhanced post-treatment resting-state functional connectivity between the amygdala, orbitofrontal cortex, hippocampus and the medial PFC.…”
Section: Introductionmentioning
confidence: 99%